What Do Job Insecure People Do? Examining Employee Behaviors and Their Implications for Well-Being at a Weekly Basis - Lopez-Bohle, S; Muñoz-Medina, L (Cambridge University Press, 2024)
The current study investigated employees weekly responses to experienced job insecurity. Based on appraisal theory, it was postulated that employees may adopt three coping strategies in response to job insecurity (i.e., remaining silent, adapting, or being proactive) in order to maintain or improve their weekly well-being. We introduced a multilevel moderated mediation model, explaining how weekly job insecurity would be related to well-being in the following weeks through these three behaviors. We also expected that subordinate emotional regulation and supervisor prosocial motivation (both defined as trait variables) would function as contextual factors moderating the relationships of job insecurity with employee behavior and well-being. A 5-week diary study of 149 subordinates partially supported the model. The results showed longitudinal conditional indirect effects of job insecurity on subordinate well-being depending on subordinate emotional regulation style and supervisor prosocial motivation. In doing so, the study offers two main contributions to the job insecurity literature. First, employees are not passive responders to perceived job insecurity, but active shapers through coping depending on the context. Subordinates emotional regulation strategy and supervisors prosocial motivation, as trait variables, impact on how subordinates respond to perceived job insecurity over weeks. From a practical point of view, the dynamic nature of perceived job insecurity suggests implications for interventions to maintain subordinates well-being. © © Cambridge University Press and Australian and New Zealand Academy of Management 2022.
Keywords: Adaptivity; employee well-being; job insecurity; proactivity; silence; weekly diary study